EVALUATION OF AQUIFER PROTECTIVE CAPACITY OF GROUND WATER RESOURCES IN BOGORO LOCAL GOVERNMENT AREA OF BAUCHI STATE, NORTHEASTERN NIGERIA - JOSEPH A., BULUS; SHOLA C., ODEWUMI (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY (2536-6041), 2020)
The study focuses on the evaluation of aquifer protective capacity of ground water resources in Bogoro area. Forty-four (44) Vertical Electrical Soundings (VES) were carried out using the Schlumberger electrode array configuration, with half-current electrode separation (AB/2) varying from 1 to 125 m using Allied Ohmega terrameter and its accessories. The curve types obtained include: A, H, K, QH, HK, KH and HKH types. The geoelectric sections indicate that the subsurface is characterized into four geoelectric layers namely: topsoil, clayey layer, fractured basement and fresh basement. The longitudinal conductance (S) values ranged from 0.006383 to 1.295251 mhos; hence, the area is classified into poor (< 0.1mhos), weak (0.1-0.19 mhos), moderate (0.2-0.69 mhos) and good (> 0.7 mhos) protective capacity. The total transverse resistance ranges from 259.6 to 24354.6Ω m2 and the electric anisotropy ranges from 0.557592 to 3.069103. The overburden thickness varies from 1.7 to 41.6 m and the map of the overburden thickness with secondary geoelectric (Dar-Zarrouk) parameters revealed that the delineated areas have productive aquiferous groundwater potentials. The major aquifer delineated in the area is the fractured basement and characterized by thick overburden with high value of longitudinal conductance (S) of moderate to good protective capacity. The aquifers exhibit moderate to relatively low value of coefficients of electrical anisotropy with high value transverse unit resistance. This attests to thick aquifer with thick clay materials above the aquifer that act as seal and high transmissivity’s while areas with poor to weak protective capacity are susceptible to infiltrating contaminating fluid.